Pengaruh Live Streaming dan Diskon Harga Terhadap Keputusan Pembelian Konsumen Lazada di Cengkareng - Aditya Permana Putra; Henny Armaniah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Information technology is developing very rapidly, including in carrying out buying and selling transactions. Traditional businesses that require face-to-face meetings are starting to be abandoned, and replaced by online marketing or what is usually called e-commerce. Lazada's sales figures are quite low compared to other e-commerce. These low sales indicate Lazada's low consumer decision. Therefore, this research was conducted to analyze the influence of live streaming and price discounts on purchasing decisions of Lazada consumers in Cengkareng. The research method applied in this research is descriptive quantitative statistics. The population in this study were Cengkareng residents with an unknown population size, but 96 Cengkareng residents were taken as samples. Data analysis techniques are data quality testing, classical assumption testing, multiple linear regression, hypothesis testing, coefficient of determination testing. Then from the research results it was found that partially Live Streaming had a positive and significant influence on purchasing decisions, price discounts had a positive and significant influence on purchasing decisions, live streaming and price discounts together or simultaneously had an influence on consumer purchasing decisions. It is known that the coefficient of determination value reaches 0.490 and it can be concluded that simultaneously, live streaming and price discounts contribute 49% to purchasing decisions, while the remaining 51% is influenced by other factors not included in this research.